An experimental and numerical study on the crush behaviour of hybrid unidirectional/woven carbon-fibre reinforced composite laminates. (December 2019) - Liu, Haibao; Falzon, Brian G.; Dear, John P.
Highlights: A computational model, which accounts for both interlaminar and intralaminar damage, was implemented as a user subroutine in Abaqus/Explicit to model the crush behaviour of hybrid unidirectional (UD)/woven composite laminates. Hybrid unidirectional (UD)/woven carbon-fibre reinforced composite specimens with two different trigger geometries; a bevel-trigger and a steeple-trigger were tested for crashworthiness assessments. A comparison between experimental and numerical results was performed to confirm the computational tool's accuracy in predicting the energy absorption and damage mechanisms of the tested specimens. The usage of this predictive model will increase the design efficiency of composite structures required to meet specific crashworthiness standards. Abstract: In composite aircraft structures, woven carbon-fibre reinforced plies are often used as the surface plies of a monolithic composite panel, made from unidirectional plies, to mitigate damage during drilling and provide a measure of impact damage resistance. This research presents, for the first time, a detailed experimental and numerical study on the crush behaviour of hybrid unidirectional/woven carbon-fibre reinforced composite laminates. Quasi-static crush tests are performed on composite specimens with two different trigger geometries; a bevel-trigger and a steeple-trigger. A computational model, which accounts for both interlaminar and intralaminar damage in hybrid unidirectional (UD)/woven composite laminates, implemented as a user subroutine in Abaqus/Explicit, was used. A comparison between experimental and numerical results confirms the computational tool's accuracy in predicting the energy absorption and damage mechanisms of hybrid specimens. The proposed approach could significantly reduce the extent of physical testing required in the development of crashworthy structures. Graphical abstract: Image, graphical abstract